Controlling the use of Tobacco for Sustainable Development: A Focus on India and South Africa - Duxbury, Theodore; Rath, Seema; Maraj, Paayal; Bosman, Sean James; Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
The use of tobacco containing products is a global health and economic burden adversely affecting sustainable development, particularly in the developing world. This article focuses on the impact of population growth, aging, gender, culture, and the ascendancy of transnational tobacco companies on the tobacco epidemic in India and South Africa. There is a distinctive manifestation of the tobacco epidemic in India and South Africa based on the stated impacting factors. Successful implementation and execution of tobacco control policies are required to promote sustainable human development. These must act in conjunction with strengthened World Health Organization tobacco control measures and improved understandings of tobacco industry strategies, as well as take population attitudes and practices towards tobacco consumption into consideration. One of the most effective contributions to controlling the tobacco epidemic is seen in health promotion initiatives.
Keywords: Tobacco; Health; Health Promotion; Sustainable Development Goals; Tobacco control polices